2016
DOI: 10.1007/s11102-016-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

“Micromegaly”: an update on the prevalence of acromegaly with apparently normal GH secretion in the modern era

Abstract: Our data show that a substantial percentage of patients with clinical acromegaly have "normal" GH, and therefore strengthens the growing body of evidence which supports the leading role of IGF-1 levels in diagnostic evaluation. At the present time, questions about the natural course of "micromegaly" and treatment benefits compared to the subpopulation with elevated GH levels remain unanswered, but research continues to build on our understanding of the heterogeneous population of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 17 publications
3
43
2
4
Order By: Relevance
“…It has long been noted that older patients with acromegaly can have milder disease features and hormonal abnormalities ( van der Lely et al 1992 ). More recently, it has been noted that a group of patients with ‘normal’ GH and elevated IGF-1 exists, that are older and have smaller tumors than acromegaly patients with typically raised GH and IGF-1 parameters ( Dimaraki et al 2002 , Butz et al 2016 ). It may be that the wider access to MRI and greater awareness noted above is also leading to increased pick-up of a milder phenotype of acromegaly in an older population.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been noted that older patients with acromegaly can have milder disease features and hormonal abnormalities ( van der Lely et al 1992 ). More recently, it has been noted that a group of patients with ‘normal’ GH and elevated IGF-1 exists, that are older and have smaller tumors than acromegaly patients with typically raised GH and IGF-1 parameters ( Dimaraki et al 2002 , Butz et al 2016 ). It may be that the wider access to MRI and greater awareness noted above is also leading to increased pick-up of a milder phenotype of acromegaly in an older population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with clinically active acromegaly and elevated IGF-1 may still have ‘suppressible’ GH after OGTT using both cut-offs of 1 and 0.4 ng/dL. These discordant findings were observed in 18–45% of treatment-naïve patients with acromegaly, 33 , 34 and in 17–35% of patients with acromegaly after treatment (surgery, radiotherapy and/or medication). 35 37 Recent studies showed that a large number of patients with acromegaly can have a very different clinical, biochemical and radiological presentation compared with what is considered a ‘classical’ one.…”
Section: Screening and Diagnosismentioning
confidence: 98%
“…In a recent series report, 31% of 157 treatment-naive patients with acromegaly had elevated IGF-1 and normal 24 hours mean plasma GH levels. The percentage of GH/IGF-1 discrepancy has increased to 47% in more recent years [27]. Newer GH assays, which are based on monoclonal antibodies with higher specificity, tend to be more sensitive when compared with older polyclonal antisera.…”
Section: Discussionmentioning
confidence: 99%